2013
DOI: 10.1039/c3ra44038a
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic helping organic: recent advances in catalytic heterogeneous oxidations by immobilised tetrapyrrolic macrocycles in micro and mesoporous supports

Abstract: This review considers several aspects (synthetic procedures and, particularly, catalytic applications) of the recent literature (since 2000) regarding the immobilisation of tetrapyrrolic macrocycles (namely porphyrins and phthalocyanines) in micro (NaY and NaX zeolites) and mesoporous inorganic supports (M41S family), and their employment in catalysis, predominantly in oxidation. Emphasis is placed on photocatalysis, which is of importance in the degradation of pesticides, herbicides, health care, personal car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
31
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 64 publications
(33 citation statements)
references
References 64 publications
1
31
0
1
Order By: Relevance
“…The immobilization of homogeneous catalysts on various insoluble supports such as a siliceous material makes the immobilized catalyst insoluble in the reaction solution, providing great advantages for the easy separation of the catalyst from the reaction mixture, the fast isolation of the reaction products, and catalyst recovery and recycling by simple filtration . The immobilization of homogeneous catalysts also allows insoluble catalysts, which would otherwise be aggregated, to be well dispersed in the reaction medium such as water, resulting in the significant enhancement in the catalytic activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The immobilization of homogeneous catalysts on various insoluble supports such as a siliceous material makes the immobilized catalyst insoluble in the reaction solution, providing great advantages for the easy separation of the catalyst from the reaction mixture, the fast isolation of the reaction products, and catalyst recovery and recycling by simple filtration . The immobilization of homogeneous catalysts also allows insoluble catalysts, which would otherwise be aggregated, to be well dispersed in the reaction medium such as water, resulting in the significant enhancement in the catalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the supported catalyst may be more sterically hindered and hence less accessible to substrates as compared to its non‐supported counterpart, while the selectivity may be enhanced by the steric effect. Catalyst instability in the homogeneous phase is mainly caused by bimolecular deactivation pathways, which are prevented by immobilization of the catalyst to isolate the catalyst reactive sites …”
Section: Introductionmentioning
confidence: 99%
“…[6,7,1] Thus, the development and optimization of new organic molecules bearing fluorine atoms in their constitution is an area of increasing interest in medicinal chemistry. In addition, in our previous studies [8][9][10], we have demonstrated that the presence of fluorine atoms in a sulfonamide-tetrapyrrolic macrocycles originated photosensitizers with ideal PDT photophysical properties and/or remarkable photostability [11][12][13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 97%
“…Halides, quaternary salts and ionic liquids are known to produce preferentially cyclic carbonates, which are the most stable thermodynamic products [9], while metal complexes can catalyze the formation of polymers and/or cyclic carbonate products, depending from the co-catalyst, substrate and reaction conditions [9]. It should be mentioned that most of the metal based complexes, of which tetrapyrrolic macrocycles are privileged compounds for many applications [13,14,15,16,17,18,19,20,21], require the presence of a co-catalyst, acting as nucleophile, whether added to the reaction (binary catalytic systems) [22,23,24,25] or already included in the structure of the complex (bifunctional catalytic systems) [26].…”
Section: Introductionmentioning
confidence: 99%